EMOTION REGULATION COMMUNITY SERVICE PROGRAM FOR COMMUNITY WORKERS AT YAYASAN QAHAL CERIA, NORTH JAKARTA: A CASE REPORT - Mariana, Foo; Putri, Angesty (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Abstract Community workers mentoring children from low-socioeconomic backgrounds often face stress, fatigue, and burnout, affecting their ability to provide consistent support. This study evaluated a culturally adapted, three-session emotional regulation (ER) programprogram for ten Indonesian community workers (aged 17–42) in an urban tutoring initiative. A mixed-methods case study design was employed, incorporating pre- and post-intervention assessments using the Emotion Regulation Questionnaire (ERQ), baseline measures from the Depression, Anxiety, and Stress Scales (DASS-42) and the Adverse Childhood Experiences Questionnaire (ACE-Q), as well as post-program reflective interviews. The intervention combined psychoeducation, role-play to practice cognitive Reappraisal and supportive responses, and art-based expression to externalize and label affect. Quantitative results showed significant increases in Cognitive Reappraisal (d = 1.52) and decreases in expressive suppression (d = –3.62), both with large effect sizes. Qualitative analysis identified four themes: increased emotional awareness, application of Reappraisal strategies, improved stress management and self-care, and challenges in sustaining change. Integrated findings indicated convergence between score improvements and reported experiences. Despite the small sample size, the findings underscore the importance of brief, culturally tailored interventions for non‑professional helpers. The results suggest that short, targeted ER programcan enhance adaptive emotional strategies and well-being among community workers in low-resource settings, with the potential to improve the quality and sustainability of educational and psychosocial services for vulnerable children. Keywords: emotional regulation, community workers, low socioeconomic status, cognitive reappraisal, expressive suppression